Experimental investigation of particle concentration using mass and optical methods - Baltrenas, Pranas; Kvasauskas, Mindaugas (Journal of Environmental Engineering and Landscape Management, 2005)
Devices of various design and measuring methods are applied for determining particle matter (PM) concentration. Therefore, it is important to know measuring precision of different measuring devices. Measurements were carried out by a recognized and widely used mass as well as the optical method. Materials commonly occurring in technological processes were used for investigation: particles of wood, cement, quartz sand and metal from polishing processes, clay and charcoal particles. Besides, the concentration of PM at one of the most bustling crossroads of Vilnius city was measured to estimate and compare the results of the mentioned methods and evaluate their suitability for measuring very low concentrations of PM. Measuring results of PM concentration are compared and estimated in this work, and coefficients, showing measuring differences among different devices and methods, are given and measuring errors are rated.Eksperimentiniai dalelių koncentracijų tyrimai taikant svorinį ir optinį metodusSantrauka. Kietųjų dalelių (KD) koncentracijoms matuoti naudojami skirtingos konstrukcijos, skirtingais matavimo metodais pagrįsti prietaisai. Todėl svarbu žinoti jų tikslumą. Matavimai buvo atlikti pripažintu ir plačiai taikomu svoriniu bei kartu optiniu metodu. Tyrimams naudotos dažniausiai technologiniuose procesuose pasitaikančios medžiagos: medienos dalelės, cementas, kvarcinis smėlis, metalo dalelės, atsirandančios šlifavimo procese, molio ir medžio anglies dalelės. Taip pat buvo išmatuotos KD koncentracijos prie vienos iš judriausių Vilniaus sankryžų. Siekta patikrinti prietaisų ir metodų tinkamumą matuoti labai mažas dalelių koncentracijas. Darbe pateikti matavimo rezultatai ir paklaidos, palyginami koeficientai, rodantys matavimo skirtingais prietaisais ir metodais skirtumus.Reikšminiai žodžiai: svorinis metodas, optinis metodas, kietosios dalelės (KD).First Published Online: 14 Oct 2010